Relationship between left atrial appendage peak flow velocity and nonvalvular atrial fibrillation recurrence after cryoablation - Wang, Long; Zhang, Yan; Zhou, Wei; Chen, Jingjing; Li, Yongkang; Tang, Qian; Chen, Bingxiu; Zhang, Huiling; Zellmer, Lucas; Chen, Jin; Chen, Zhangrong; Li, Wei; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Previous studies revealed the connection between left atrial appendage peak flow velocity (LAA-PEV) and postoperative persistent atrial fibrillation (AF) recurrence. Yet, this association is not necessarily generalizable to persistent AF patients undergoing initial cryoballoon ablation due to current gaps in the literature. Methods We prospectively studied 74 consecutive individuals with persistent atrial fibrillation undergoing a cryoballoon ablation for the first time between January 2018 and January 2020. Before ablation, LAA-PEV was documented by transesophageal echocardiography (TEE). Subsequently, demographic information and other clinical characteristics of these participants were collected. A 96-h continuous cardiac monitor was reviewed regularly for recurrence of atrial fibrillation. Cox proportional hazards regression was used to investigate LAA-PEV as well as other clinical characteristics as a predictor of AF recurrence. Results Our study found that AF recurrences had lower LAA-PEV than those without AF recurrence. A nonlinear relationship between the LAA-PEV and AF recurrence was observed in this study, which had an inflection point of 34.9. Subgroup analysis of female participants showed that LAA-PEV had a positive correlation with AF recurrence [β = 0.8, 95% CI (0.7, 0.9), p < 0.05]. Conclusion A low LAA-PEV is related to recurrence of atrial fibrillation and may predict AF recurrence after initial cryoballoon ablation for persistent atrial fibrillation. This finding may help improve treatment and care strategies for patients with persistent atrial fibrillation.